Recent trends of biotechnological production of polyhydroxyalkanoates from C1 carbon sources - Ray, Subhasree; Jin, Jun-O; Choi, Inho; Kim, Myunghee (Frontiers in Bioengineering and Biotechnology, 2023)
Growing concerns over the use of limited fossil fuels and their negative impacts on the ecological niches have facilitated the exploration of alternative routes. The use of conventional plastic material also negatively impacts the environment. One such green alternative is polyhydroxyalkanoates, which are biodegradable, biocompatible, and environmentally friendly. Recently, researchers have focused on the utilization of waste gases particularly those belonging to C1 sources derived directly from industries and anthropogenic activities, such as carbon dioxide, methane, and methanol as the substrate for polyhydroxyalkanoates production. Consequently, several microorganisms have been exploited to utilize waste gases for their growth and biopolymer accumulation. Methylotrophs such as Methylobacterium organophilum produced highest amount of PHA up to 88% using CH4 as the sole carbon source and 52–56% with CH3OH. On the other hand Cupriavidus necator, produced 71–81% of PHA by utilizing CO and CO2 as a substrate. The present review shows the potential of waste gas valorization as a promising solution for the sustainable production of polyhydroxyalkanoates. Key bottlenecks towards the usage of gaseous substrates obstructing their realization on a large scale and the possible technological solutions were also highlighted. Several strategies for PHA production using C1 gases through fermentation and metabolic engineering approaches are discussed. Microbes such as autotrophs, acetogens, and methanotrophs can produce PHA from CO2, CO, and CH4. Therefore, this article presents a vision of C1 gas into bioplastics are prospective strategies with promising potential application, and aspects related to the sustainability of the system.